Discussing the Reform of Physical Education Instruction Based on the Basic Skills Competition for Physical Education Majors in Chongqing Municipality’s General Colleges and Universities - Cheng, Guangxin; Zhongchen Zhang; Zhiming Shi (Journal of Education, Health and Sport, 2025)
Purpose:In order to provide theoretical support for the basic skills competition of college and university students, the reform of physical education instruction in colleges and universities, and the talent development system for physical education majors, we analyze and research the basic skills competition in order to identify the issues that currently exist and propose solutions. Methodology:The fundamental skills competition of physical education majors in regular higher education institutions in Chongqing in 2024 is thoroughly examined in this study using the literature approach, mathematical statistics method, observation method, and comparative analysis method. Description of state of knowledge: A test of college and university physical education majors’ training, the basic skills competition serves as a vital platform for advancing the caliber of college and university physical education majors, the caliber of students’ physical education instruction, the depth of physical education majors’ training, and the overall proficiency of students. Conclusion:1. It is necessary to enhance the competition elements and score weighting, as well as to reinforce the uniformity of the student selection process and judging criteria. 2. Improve the basic skills competition’s content and score distribution, create a scientific method for choosing pupils to compete, and fortify the impartiality of the performance evaluation criteria. 3. In order to increase the learning motivation of college and university students studying physical education, it is important to emphasize the value of teaching the fundamentals of various physical education topics. Additionally, the teaching of physical education should improve students’ practical and application skills.